An Objective Structured Clinical Examination to Assess Problem-Based Learning - Salinitri, Francine D. (American Journal of Pharmaceutical Education, 2012)
Objectives. To compare pharmacy students’ performance on an objective structured clinical examination (OSCE) to their performance on a written examination for the assessment of problem-based learning (PBL); and to determine students’ and faculty members’ perceptions of OSCEs for PBL evaluations. Design. Four OSCEs were added to the written examination to assess 4 PBL cases in a third-year pharmacotherapy course. OSCE scores were compared to written examination scores. Faculty members evaluated student performance. Assessment. OSCE performance did not correlate with the written-examination scores. Most students (≥ 75%) agreed that OSCEs reflected their learning from PBL and measured knowledge, communication, and clinical skills. A majority of faculty members (≥75%) agreed that OSCEs should be part of PBL assessment. Conclusions. Addition of an OSCE to written examinations was valued and provided a more comprehensive assessment of the PBL experience.